PERSUASIF PADA SPANDUK PILKADADI KABUPATEN MERANGIN TAHUN 2017-2018 - Helsa Aprillia; Baitullah . (Jurnal Tunas Pendidikan, 2019)
Political communication cannot be separated from the use of language that leads to the delivery of messages, appeals, hopes, requests, and desires for influence. The forms of speech that exist in political communication, especially the regional head election banners (Pilkada) have different characteristics from the speech in ordinary communication or other political communication. Therefore, every human being should not only understand what the Election banner has said, but also the context used in the utterance must be understood. This study aims to describe the form of sentences and persuasive techniques used in the 2017 local election banner in Merangin District. The approach used in this study is a qualitative approach. The data source in this study was the 2017 Local Election banner in Merangin Regency, which amounted to 14 banners. In this study, the data examined were sentences contained in the 2017 local elections banner in Merangin Regency. To collect research data, researchers used documentation techniques, namely the 2017 regional election banners in Merangin District, which were collected in the form of photographs. Based on the process of data collection and data analysis that researchers have done, researchers obtain data that there are 7 types of news sentences, 4 types of exciting sentences, and 3 types of command sentences. Meanwhile, there were 5 banner sentences that used identification techniques, 1 rationalization technique, 1 suggestion technique, and 7 compensation techniques. The use of persuasive techniques or sentence forms on these banners aims to get the attention of the readers and influence the emotions, thoughts, and feelings of the wider community who also read the banners. Based on these findings the researcher suggests that political parties are expected to provide banners containing educative and constructive matters